62‐2: Flexible Full‐Color Active‐Matrix Quantum‐Dot OLED Display. Issue 1 (28th June 2021) - Huang, Wei; Jin, Qian; Zhao, Dejiang; Sun, Zhongyuan; Li, Wei; Shu, Shi; Sun, Qian; Tian, Yu; Zhang, Juan; An, Che; Wang, Linlin; Jiao, Zhiqiang; et al.
Abstract : Quantum dot display with blue light excitation has attracted a lot of attention recently. In this work, rigid 13.6 inch 1920×1080 FHD full color active matrix quantum dot OLED display (QDOLED) on glass substrate and another evolutional flexible Quantum dot Filter On Electroluminescence display (QFOE) on polyimide (PI) substrate were fabricated with different device configuration. Cd‐free InP QD was introduced into photo‐curable resin and patterned by inkjet‐printing or photolithography process as the color conversion material (CCM). The 2‐stack blue OLED (B‐OLED) device designed under the balance of efficiency and uniformity was employed to excite QD pixel patterns by active matrix driving of coplanar oxide thin‐film transistor (TFT) backplane. The display performances of wide viewing angle, high color purity and excellent contrast ratio are preserved after the flexible process integration into QFOE to show more application potentials in near future.